Exacavating the Memory of Slavery in Léonora Miano’s La Saison de l’ombre (2013) and Toni Morrison’s Beloved (1988) - SENE, Abib; Keïta, Fatoumata (International Journal of Language and Literary Studies, 2021)
Regarded as a state of servitude through which an individual or a group of persons is compelled to work their guts out without any possibility to get compensated or rewarded, slavery, for some centuries, had been implemented under various forms from one country to another. From the antiquity to the twentieth century, thralldom had been a profitable business that gangrened the African continent. Thus being, African and African American thinkers shoulder the mission to dust archives and lift the curtain of history to retell and re-narrate the episode of drudgery; among them Leonoa Miano and Toni Morrison. The purpose of this article is to examine the trauma of slavery from a comparative, matrifocal, and Afrocentric perspective so as to highlight commonalities and differences between Leonora Miano’s La Saison de l’ombre and Toni Morrison’s Beloved. Inspired by the infamous history of slavery, these two award-winning novels not only conjure up the ordeal of slavery, but they also catalyze its haunting memory for the sake of healing, so that both characters and readers could be cleansed off its tantalizing grip and achieve catharsis and redemption. To this end, La Saison de l’ombre and Beloved are woven around feminine counter-narratives that exhibit counter-memories which are often glossed over or overlooked in both African and Euro-American phallocentric official narratives. Whereas La Saison de l’ombre spotlights the Africans’ role in the process of slavery, Beloved highlights the tragedy of a maternal love in a context of bondage. Through a comparative approach, we have spotlighted the whole process of slavery, from the captivity in Africa to enslavement in America.